A Different Perspective on Migration - Ćorić, Dragana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
Population is one of the three key elements for constituting the state, together with the territory and the state government. Without a population, as well as without a territory or a government, a state cannot exist, but exists only as a society with a loose structure. In this paper, we argue that, although migrations change the internal structure of the population within one country and do so globally, at the same time, they cannot cause a loss of state status. Changing its internal structure may lead to the redefinition of some internal state’s policies, but by no means can migrations destroy the concept of the state. Careful monitoring of migration flows and tendencies is an opportunity for the development of a specific country or for changing its foreign policy (when it comes to interstate migration). Migrations, both domestic and international, are shaping the modern world in a different way than ever before. The history of migration and population movement over the last 50 years has shown different tendencies, reasons and conditions for their development.